2010
DOI: 10.1111/j.1537-2995.2010.02645.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of antibody‐opsonized red blood cells results in a shift in the immune response from the red blood cell to the antibody in a murine model

Abstract: This work demonstrates that, under AMIS conditions, the IgG itself becomes the focus of B cells in the immune system, suggesting a potential mechanism of B-cell regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
(61 reference statements)
2
14
0
Order By: Relevance
“…In the AMID work, mice were injected with SRBCs or the diphtheria/ tetanus vaccine in the presence versus absence of Ag-specific IgG. We observed that under conditions in which the IgG successfully mediated an AMIS effect against the Ag, a dose-dependent humoral immune response against the AMIS-inducing IgG was observed (5). These Abs (anti-IgG) observed in our prior work somewhat resemble rheumatoid-like factors, which may themselves be immune regulatory, or their appearance could simply be an indication of immune deviation away from the original Ag.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the AMID work, mice were injected with SRBCs or the diphtheria/ tetanus vaccine in the presence versus absence of Ag-specific IgG. We observed that under conditions in which the IgG successfully mediated an AMIS effect against the Ag, a dose-dependent humoral immune response against the AMIS-inducing IgG was observed (5). These Abs (anti-IgG) observed in our prior work somewhat resemble rheumatoid-like factors, which may themselves be immune regulatory, or their appearance could simply be an indication of immune deviation away from the original Ag.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a variety of other hypotheses can explain AMIS induction (Table I). Although any of these hypotheses could potentially be responsible for AMIS effects, our recent finding of AMID being related to AMIS induction is of interest (5). In the AMID work, mice were injected with SRBCs or the diphtheria/ tetanus vaccine in the presence versus absence of Ag-specific IgG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations